First-principles study on the electronic structure, magnetic properties, elastic constants and sound velocity of the monoclinic crystal BiNiO3 under pressure - Li-Ke Gao; Xiao-Si Qi; Yan-Lin Tang (Results in Physics, 2024)
BiNiO3 is a perovskite material with potential applications in various fields. In this paper, the crystal structure, electronic structure and elastic constants of monoclinic BiNiO3 under different pressure have been studied by first-principles. The results show that applying pressure causes changes in bond length between atoms and crystal structure, and can cause electrons to transfer between atoms. In particular, the valence states of Bi and Ni may change. These changes may lead to the transformation of the material from a monoclinic structure to an orthorhombic structure. Under the action of pressure, the magnetic moment decreases from 1.00 μB to about 0.50 μB, and the decrease is the largest in the range of 5 ∼ 15 GPa, which indicates that the pressure has an effective modulation effect on the magnetic moment. In addition, the influence of pressure on the elastic constant is studied. The results show that pressure has a significant effect on the elastic constants along the matrix diagonal, and the elastic constant increases with the increase of pressure. Finally, the changes of sound velocity on the crystal planes [100], [010] and [001] of monoclinic crystal structure under pressure are also studied, and it is found that pressure can effectively regulate sound velocity. This study shows that the crystal structure and electromagnetic properties of BiNiO3 can be regulated by pressure.